2019
DOI: 10.1177/0363546518818820
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lateral Meniscus Posterior Root Tears in the Anterior Cruciate Ligament–Injured Knee: An Epidemiological Analysis of 3956 Patients From the SANTI Study Group

Abstract: 8Background: Lateral meniscal posterior root tears (LMPRT) result in loss of hoop forces 9 and significant increases in tibiofemoral contact pressures. Pre-operative imaging lacks 10 reliability and therefore holding an appropriate index of suspicion, based on the 11 epidemiology and risk factors for LMPRT, may reduce the rate of missed diagnoses. 12 Hypothesis/Purpose: The primary objectives of this study were to evaluate the incidence 13 and risk factors for lateral meniscus root lesions in a large series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
79
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 38 publications
(84 reference statements)
2
79
0
2
Order By: Relevance
“…This could be due to the fact that 93% of our patients were recreational or competitive athletes, and our patients were younger on average than other studies. 3,18,20 The mechanism for these posterior horn lateral meniscal tears is likely the pivot-shift phenomenon, where subluxation in the lateral compartment of the lateral femoral condyle compresses a The number of tears is larger than number of patients with tear because some patients had bilateral tears or multiple tears on 1 meniscus. the posterior horn of the lateral meniscus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the fact that 93% of our patients were recreational or competitive athletes, and our patients were younger on average than other studies. 3,18,20 The mechanism for these posterior horn lateral meniscal tears is likely the pivot-shift phenomenon, where subluxation in the lateral compartment of the lateral femoral condyle compresses a The number of tears is larger than number of patients with tear because some patients had bilateral tears or multiple tears on 1 meniscus. the posterior horn of the lateral meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,12,13,17,24 Studies have reported the incidence of meniscal tears associated with ACL tears to range between 47% and 65%. 1,7,9,14,18,19 Unlike medial meniscal tears, which commonly occur chronically after ACL injury, lateral meniscal tears occur most commonly with acute ACL injuries. 4,5,7,8 Posterior meniscal tears commonly occur concurrently with ACL injuries.…”
mentioning
confidence: 99%
“…Few publications have evaluated the kinematic and biomechanical effects of a PLMRT compared to a PMMRT 13 ; however, interest in this subject is increasing. A recent study 21 evaluating 3956 patients undergoing ACL reconstruction performed an epidemiological analysis of PLMRTs, which were identified in 6.6% of the cases. In addition, multivariate analysis showed that participation in contact sports and associated medial meniscus tears are independent risk factors for PLMRTs.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that radial tears or avulsions at the posterior LM root are found in up to 7% to 12% of patients with ACL tears 2, 3. These tears present unique surgical challenges with particular biomechanical consequences 4 .…”
mentioning
confidence: 99%
“…LM root tears are likely underrecognized because they are easily missed in preoperative magnetic resonance imaging (MRI) scans 5 . It is critical to have a high suspicion of tears in the setting of ACL injury, particularly in patients with greater tibia varus angles, increased tibial slopes, higher body mass index, contact injuries, and concomitant medial meniscus tears 3, 6. Although uncommon, it is possible to have coexisting radial tears of the posterior horn or root and of the body of the LM secondary to a combined ACL-MCL injury.…”
mentioning
confidence: 99%